2014
DOI: 10.1061/(asce)cc.1943-5614.0000442
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Shear Behavior of Reinforced-Concrete Members Fully Wrapped with Large Rupture-Strain FRP Composites

Abstract: Experimental study on shear behavior of reinforced concrete members fully wrapped with large rupture strain FRP composites This paper presents an experimental study on the shear behavior of reinforced concrete (RC) members fully wrapped with polyethylene terephthalate (PET) fiber reinforced polymer (FRP) composites, which are a new type of FRP material characterized with a much larger rupture strain (LRS) compared to conventional FRPs (i.e., made of carbon, glass, and aramid fibers). A total of ten PET fully-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 18 publications
(11 reference statements)
1
12
0
Order By: Relevance
“…This phenomenon was first observed in FRP-wrapped columns under cyclic loading (Priestley et al, 1996;Priestley and Seible, 1995). More recently, the existence of this adverse shear interaction was clearly observed by Jirawattanasomkul Jirawattanasomkul et al (2013) in RC beams shear-strengthened by FRP wraps and by Chen et al (2016) in RC beams shear-strengthened with well-anchored FRP U-strips (failing by FRP rupture). Using accurately measured FRP strains, it was shown that the concrete shear contribution started to decrease while that of FRP was still increasing.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…This phenomenon was first observed in FRP-wrapped columns under cyclic loading (Priestley et al, 1996;Priestley and Seible, 1995). More recently, the existence of this adverse shear interaction was clearly observed by Jirawattanasomkul Jirawattanasomkul et al (2013) in RC beams shear-strengthened by FRP wraps and by Chen et al (2016) in RC beams shear-strengthened with well-anchored FRP U-strips (failing by FRP rupture). Using accurately measured FRP strains, it was shown that the concrete shear contribution started to decrease while that of FRP was still increasing.…”
Section: Introductionmentioning
confidence: 85%
“…RC beams shear-strengthened with FRP side strips, or strengthened with U-strips predominantly fail due to the debonding of FRP strips from the beam sides (Chen and Teng, 2003a, b;). However, often the failure of RC beams shear strengthened with FRP wraps (Jirawattanasomkul et al, 2013; and in some cases with FRP U-jackets [e.g. FRP U-jackets with anchorage (Chen et al, 2016;Kim et al, 2014;Mofidi et al, 2012)], are due to the rupture of FRP, usually preceded by FRP debonding (Cao et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past three decades, the FRP repair and strengthening technique has been extensively used in practice and evaluated by many experimental research activities focusing on improving the confining properties, ductility and strength [9], [40], [42], [49]- [52], [54]. However, very limited experimental research has given attention to assessing the validity of FRP repair of RC bridge columns using the dynamic testing with shaking [28], [60]. To the best of author's knowledge no such dynamic load assessment exists in the literature considering the realistic combined effect of lateral and vertical ground motion excitations.…”
Section: List Of Tablesmentioning
confidence: 99%
“…However, due to low fracturing strain capacity of conventional FRPs [around 1.5% for carbon FRP (CFRP), 2% for glass FRP (GFRP), and 3% for aramid FRP (AFRP)], the fiber materials tend to fail sooner due to fiber breakage, which causes a loss of confinement and hence the load-carrying capacity as well as the ductility potential. New fiber materials, such as polyacetal fiber (PAF), polyethylene naphthalate (PEN), and polyethylene terephthalate (PET), have properties of large fracturing strain and low stiffness in comparison to aramid, carbon, and glass fibers (Jirawattanasomkul, Dai, Zhang, Senda, & Ueda, 2013). Previous studies (Anggawidjaja, Ueda, Dai, & Nakai, 2006;Dai, Bai, & Teng, 2011;Dai, Lam, & Ueda, 2012) proved that concrete or RC members wrapped by PET and PEN fiber sheets with large fracturing strain could efficiently enhance the ductility of concrete or RC members, regardless of their low stiffness.…”
Section: Introductionmentioning
confidence: 99%